Physical active lifestyle promotes static and dynamic balance performance in young and older adults - Sarto, Fabio; Pizzichemi, Martina; Chiossi, Francesco; Bisiacchi, Patrizia S.; Franchi, Martino V; Narici, Marco V; Monti, Elena; Paoli, Antonio; Marcolin, Giuseppe (Frontiers in Physiology, 2022)
Although regular physical activity exposure leads to positive postural balance control (PBC) adaptations, few studies investigated its effects, or the one of inactivity, on PBC in populations of different age groups. Thus, this study investigated the impact of a physically active lifestyle on static and dynamic PBC in young and older adults. Thirty-five young physically active subjects (YA), 20 young sedentary subjects (YS), 16 physically active older adults (OA), and 15 sedentary older adults (OS) underwent a static and a dynamic PBC assessment. A force platform and an instrumented proprioceptive board were employed to measure the center of pressure (COP) trajectory and the anteroposterior oscillations, respectively. In static conditions, no significant differences were detected among groups considering the overall postural balance performance represented by the area of confidence ellipse values. Conversely, the YA highlighted a higher efficiency (i.e., lower sway path mean velocity) in PBC maintenance compared to the other groups (YA vs OA: p = 0.0057, Cohen’s d = 0.94; YA vs OS p = 0.043, d = 1.07; YA vs YS p = 0.08, d = 0.67). OS exhibited an overall worse performance in dynamic conditions than YA and YS. Surprisingly, no differences were found between YS and OA for all the static and dynamic parameters considered. In conclusion, our results suggest that a physically active lifestyle may promote static and dynamic balance performance in young and older adults, thus with potentially positive effects on the age-related decline of postural balance performance. Dynamic PBC assessment seems more sensitive in detecting differences between groups than the static evaluation.